Recommendations of the clinical target volume for the para-aortic region based on the patterns of lymph node metastasis in patients with biliary tract cancer - Long, Xin; Wu, Han; Yang, Lei; Xu, Hui; Dai, Jing; Wang, Wenbo; Xia, Ling; Peng, Jin; Zhou, Fuxiang (Frontiers in Oncology, 2022)
Background: To determine the precise delineation of para aortic clinical target volume(CTV) for biliary tract cancer(BTC) according to the regularity of lymph node metastasis(LNM). Methods: The imaging records of patients with BTC from 2015 to 2020 were analyzed retrospectively. The metastasis risk for different lymph node regions was assessed. The diagnosed para aortic lymph nodes(PALNs) were manually mapped to standard axial CT images. The asymmetric CTV expansion from para aortic were defined, according to the distance from the volume center of lymph nodes to the edge of aorta. Results: A total of 251 LNMs were identified in study cohort. Group 16b1 has highest involvement rate(17%), followed by 16a2 (13%). The upper boundary of 16a2 and the lower boundary of 16b1 were defined as the superior border and the inferior border of para aortic CTV, respectively. Adding 18 mm in the front, 12 mm on the left and 24 mm on the right were defined as the optimal expansion range of para aortic CTV. The new CTV included 96% (73/76) of PALNs in 16a2 and 16b1 in study cohort and 96% (47/49) of PALNs in validation cohort. Besides, the prognosis in patients with PALN recurrence was significantly better than that in patients with other distant organ recurrence(Hazard Ratio(HR)=0.219; 95% confidence interval（CI）0.067-0.711; P=0.006). Conclusions: The involvement risk of PALN in 16a2 and 16b1 was the highest and based on the distribution of PALNs, a new para aortic CTV was defined to construct a more accurate target volume.